Alegori Politik “Kakawin Arjunawiwāha”: Penokohan Arjuna Sebagai Representasi Raja Airlangga - Galang Adhi Pradipta (Badan Riset dan Inovasi Nasional (BRIN), 2026)
Traditional historiography positions Kakawin Arjunawiwaha as a political allegory of King Airlangga, yet systematic textual evidence regarding this mechanism remains limited to philosophical and ethical dimensions. This research aims to map the narrative structure to identify character functions and reveal the ideological meaning legitimizing Airlangga's power post-crisis. Employing a qualitative method with A.J. Greimas’ structural narratology approach and dhwani theory, this study dissects the configuration of Arjuna's role. The results indicate that Arjuna's transformation through three phases—Yogi, Knight, and King—possesses a precise functional correspondence with Airlangga's political biography in restoring the kingdom following the Wurawari attack in 1006 AD. The Yogi phase represents spiritual authenticity during exile, the Knight phase symbolizes military strategy (niti) in defeating enemies, and the King phase affirms power ethics oriented toward welfare. It is concluded that Kakawin Arjunawiwaha functions as a medium of political legitimacy that reconstructs the collective memory of destruction (pralaya) into a narrative of divine resurrection, paralleling Arjuna's struggle with Airlangga's efforts to restore the world order (sthiti) and establishing his position as a legitimate ruler bearing a spiritual mandate.